Management of Zakat, Infaq, Shadaqah, and Waqf (Ziswaf) in Pondok Modern Muhammadiyah Pakusari - Dhofir Catur Bashori; Siti Khayisatuzahro Nur (Al-Iqtishadiyah: Ekonomi Syariah dan Hukum Ekonomi Syariah, 2024)
Islamic boarding schools are institutions that have two functions at once, namely educational functions and social functions. The educational function can be seen from the role of pesantren in organizing education for the community. The social function can be seen from social activities in the form of managing philanthropic funds from the community in the form of zakat, infaq, shadaqah, and waqf funds from the community. One of the boarding schools that has the potential to receive zakat, infaq, shadaqah, and waqf funds from the community is Pondok Modern Muhammadiyah Pakusari. This research aims to find out how the management of Zakat, Infaq, Shadaqah, and Waqf (ZISWAF) funds at Pondok Modern Muhammadiyah Pakusari. In addition, the research is intended to find out how the role of Pondok Modern Muhammadiyah Pakusari in fostering public awareness in channeling their generosity through pesantren in the form of payment of ZISWAF funds. This research is a field research using qualitative research methods. The results of this study indicate that the management and ZISWAF at Pondok Modern Muhammadiyah Pakusari are still conventional. There is no special Amil Zakat Institution (LAZ), so the management of zakat, infaq, shadaqah, and waqf funds is not optimal. Therefore, there needs to be a rearrangement in managing philanthropic funds in the form of zakat, infaq, shadaqah, and waqf funds at Pondok Modern Muhammadiyah Pakusari.